Circulating adiponectin levels in type 2 diabetes mellitus patients with or without non-alcoholic fatty liver disease: Results of a small, open-label, randomized controlled intervention trial in a subgroup receiving short-term exenatide. (March 2016) - Savvidou, Savvoula; Karatzidou, Kyparissia; Tsakiri, Kalliopi; Gagalis, Asterios; Hytiroglou, Prodromos; Goulis, John
Highlights: DMT2 with concomitant NAFLD is associated with a greater decrease in adiponectin. Adiponectin concentration was found to correlate negatively with the degree of ALT. Exenatide was effective in inducing weight loss and non-inferior in lowering HbA1c. Exenatide proved equally effective in increasing adiponectin levels. Increases of adiponectin were attributable to weight loss, glucose control and CRP. Abstract: Aim: Diabetes mellitus type 2 (DMT2) and non-alcoholic fatty liver disease (NAFLD) are both characterized by decreased circulating adiponectin. Recently, glucagon-like peptide-1 receptor agonists have been shown to induce adiponectin's expression. However, their interaction on clinical grounds needs to be further elucidated. Methods: DMT2 patients with abnormal aminotransferases were screened for NAFLD and subjected to liver biopsy (group A, n = 17). A subgroup of patients ( n = 110), after assessed for eligibility criteria, was blindly randomized to receive either 6-month exenatide supplementation on glargine insulin (group B) or intense, self-regulated, insulin therapy alone (group C). Results: Baseline patient characteristics: 49(38.6%) males, aged 63.1 ± 7.5 years-old, BMI 32.9 ± 4.9 kg/m 2, HbA1c 8.1 ± 1.2% (65 ± 14 mmol/mol), median ALT 23 U/L (range 5–126), AST 20 U/L (7–72). Group A had biopsy-proven NAFLD with a median Activity Score of 5 and fibrosis stage 3. Presence of NAFLD was accompanied by a significant decline in adiponectin ( p < 0.001), which was negatively correlated with the degree of ALT in all groups (Spearman's correlation, r s = −0.644, p < 0.001). In the subgroup intervention trial, adiponectin was significantly raised in both groups B and C ( t -Student for paired samples, p = 0.001) by Δ = +24.2% (interquartile range 14.8–53.2%). This elevation was not associated with the type of intervention but with weight loss, glycemic control and reduction of C-reactive protein (one-way ANCOVA). Conclusion: Supplementation of exenatide to glargine insulin compared to standard insulin was: (i) effective in inducing weight loss, (ii) non-inferior in lowering HbA1c and (iii) non-inferior in increasing circulating adiponectin. Higher adiponectin was associated with lower ALT, suggesting a hepato-protective role for this cytokine.